Corpus Linguistics and Bilingual Terminology: The AntConc Program and Term Extraction in German - Alberts-Franco, Cristina (The ESPecialist, 2015)
This paper discusses three researches involving Corpus Linguistics and Terminology German/Portuguese using program AntConc. The first aimed to extract terms related to Economics in German electronic newspapers. The second and third aimed to extract terms related to the Indian material culture in works by Koch-Grünberg; the purpose: compile a bilingual glossary. The first and second researches, using tools Word List, Concordance, and File View, shortly allowed extraction of large number of terms, whose frequency was reliably established. The third, in initial phase, will allow us to enlarge the results produced with the second, presently with 257 terms and their translation.